Investigating the content and processes of patient-derived quality of care indicators for those affected by multiple long-term conditions (MLTC): A scoping review protocol - Sara Tavares; Arad Reisberg; David Belsey; Ania Henley; Laura Downey (PLoS ONE, 2025)
Background People living with multiple long-term conditions (MLTC) are reported to have poorer quality of life, worse health outcomes, and higher health-related expenses compared to those with singular chronic health conditions. Living with MLTC is associated with a higher risk of care that is duplicate or unnecessary. Understanding and monitoring the quality of care (QoC) for those with MLTC is imperative to ensure that individuals complex care needs are met, maximising health and wellbeing and minimising harm and social/economic burden. There is paucity on what QoC means in the context of MLTC, which is likely different than a mere amalgamation of quality indicators of each contributory condition. There is even less understanding on how QoC can be measured in a way that meets the specific care priorities of individuals with MLTC. The aim of this review is to systematically map and analyse evidence on what QoC means for those affected by MLTC and the content and processes of any existing QoC indicators in MLTC, developed with patient or caregivers. Methods We will systematically search for evidence following a Levac et al methodological scoping review process. All eligible studies published in English from 2000 onwards in the following databases will be included: MEDLINE, EMBASE, CINAHL, APA PsycINFO, Global Health and Health Management Information Consortium. Given expected study heterogeneity, a narrative synthesis is anticipated. Our Community Partner Advisory Group will assist in the identification and analysis of relevant evidence. Discussion Current evidence shows variations in concepts and approaches when developing, implementing or validating QoC indicators, not always capturing patients’ preferences nor the complex processes required in MLTC care. Clarifying concepts and synthesising evidence-based knowledge in this area will be the first step to inform the development of a project aiming to develop a set of patient-derived QoC indicators for use across multiple settings in the United Kingdom (UK) and beyond. Systematic review registration Available on Open Science Framework on https://osf.io/gjr84.